Ulcerative and Spreading Nodular Lesion of Epizootic Lymphangitis in Adult Black Horse in Gondar, Ethiopia: Case Report and Wound Treatment - Balemual Abebaw (Case Reports in Veterinary Medicine)
An adult male black horse was presented to the UOG veterinary clinic with swelling, discharge, and skin wounds on the chest wall and the right front leg; then, it goes to the lateral and medial hind leg. Inspection and palpation were carried out, and we revealed that the skin was swelled, thickened and hard on clinical examination. There was also nodule rupture, and discharge on the limb and chest skin. Different therapy was applied starting from washing the wound with water-diluted potassium permanganate and then 0.9% NaCl together with paraffin topically placed on the wound. 10% povidone-iodine was also applied by using gauze. Griseofulvin 750 mg/day for one week was given as antifungal therapy orally. The prognosis was poor due to the long incubation period and high resistance of the causative agent.